Tau as a diagnostic instrument in clinical trials to predict amyloid in Alzheimer's disease - Shcherbinin, Sergey; Morris, Amanda; Higgins, Ixavier A.; Tunali, Ilke; Lu, Ming; Deveau, Carmen; Southekal, Sudeepti; Kotari, Vikas; Evans, Cynthia D.; Arora, Anupa K.; Collins, Emily C.; Pontecorvo, Michael; et al. (Alzheimer's & dementia : translational research & clinical interventions, 2023)
Alzheimer's disease (AD) is characterized by the presence of both amyloid and tau pathology. In vivo diagnosis can be made with amyloid and tau positron emission tomography (PET) imaging. Emergent evidence supports that amyloid and tau accumulation are associated and that amyloid accumulation may precede that of tau. This report further investigates the relationship between amyloid and tau to assess whether elevated cortical tau can predict elevated amyloid in participants with early symptomatic AD. Florbetapir F18 and flortaucipir F18 uptake were evaluated from baseline PET scans collected in three multi-center studies with cognitively impaired participants, including A05 ( = 306; NCT02016560), TB ( = 310; TRAILBLAZER-ALZ; NCT03367403), and TB2 ( = 1165; TRAILBLAZER-ALZ 2; NCT04437511). Images were assessed using visual and quantitative approaches to establish amyloid (A+) and tau (T+) positivity, as well as a combination method (tauVQ) to establish T+. Associations between global amyloid and tau were evaluated with positive and negative predictive values (PPV, NPV) and likelihood ratios (LR+, LR-). Predictive values within subgroups according to ethnicity, race, cognitive score, age, and sex were also evaluated. The relationship between regional tau (four target and two reference regions were tested) and global amyloid was investigated in A05 participant scans using receiver-operating characteristic (ROC) curves. PPV for amyloid positivity was ≥93% for all three trials using various A+ and T+ definitions, including visual, quantitative, and combination methods. Population characteristics did not have an impact on A+ predictability. Regional analyses (early tau (Eτ) volume of interest (VOI), temporal, parietal, frontal) revealed significant area under the ROC curve in Eτ VOI compared to frontal region, regardless of reference region and consistent among visual and quantitative A+ definitions ( < 0.001). These findings suggest that a positive tau PET scan is associated (≥93%) with amyloid positivity in individuals with early symptomatic AD, with the potential benefits of reducing clinical trial and health care expenses, radiation exposure, and participant time. Positron emission tomography (PET) evaluates candidates for Alzheimer's disease (AD) research. A positive tau PET scan is associated (≥93%) with amyloid positivity.A positive amyloid PET is not necessarily associated with tau positivity.Tau PET could be the sole diagnostic tool to confirm candidates for AD trials.